Penerapan Model Pembelajaran Kooperatif Tipe Think Talk Write Terhadap Kemampuan Penalaran Matematis Siswa Kelas XI IPA MAN Kota Padang - Irwan, Irwan; Sari, Devi Permata (Universitas Islam Negeri Imam Bonjol Padang, 2018)
The problems that occur in the field is the low of students’ mathematical reasoning abilities in the class XI IPA MAN Padang. It can be seen from the finding of observation and analysis toward the result of test given to the students. To overcome the problems, the cooperative teaching model Think Talk Write is used. The purpose of the study is to find out the effct of the cooperative teaching model Think Talk Write application toward students’ mathematical reasoning abilities in the class XI IPA MAN Padang. The research is quasy experiment. The population of the research is all students in the class XI IPA MAN Padang. The technique used for the sampling is random sampling. The sample of the reasearch is the students in the class XI IPA2 MAN 1 Padang as experiment class and the students in the class XI IPA1 MAN 1 Padang as control class. The instrument used in the reasearch is the test that consists of the first test to see the initial ability of the students and the final test to see toward students’ mathematical reasoning abilities. Based on the finding of the research, it can be concluded: first, the students’ mathematical reasoning abilities which is taught by the cooperative teaching model Think Talk Write is better than those which is taught b conventional teaching. Second, the students’ mathematical reasoning ability who have high, fair and low abilities which is taught by the cooperative teaching model Think Talk Write is better than those which is taught b conventional teaching.Keywords: Cooperative Learnig Model Think Talk Write type ,Mathematical Reasoning Ability